Inclusion: Way Forward to Redefine Classrooms - Gupta, Neha (JOURNAL OF INDIAN EDUCATION, 2019)
Disabled population form a significant but under represented minority. In the extreme past, this population was ignored and separated from the normal population of the country. With the advent of time, they attracted the focus of policy planners to frame written and planned rights for them. With the growing attention and considerations, Indian government has framed numerous policies and rules for the welfare of disabled population of the country. One of the most favored steps for them is extension of Indian Census survey to eight categories from five. Not only policy planners and framers, every citizen of the country has a sense of belongingness for disabled population. This is the generation, where we not only talk about their requirements but we also provide them all necessary amenities so that they can prosper well in their life. Owing to the growing concern about differently abled population in India, the present paper is an attempt to summarise all domains of this population. This paper discusses the population sector of differently abled with a comparative account of different types of disabilities. It also presents the concept of inclusive education to provide free and compulsory education to each and every child. Further, the paper also has various strategies to redefine a normal classroom to make it more accommodating for special children. Hence, this paper will help teachers and teacher-educators to implement and practice various practices like curricular adaptations, lesson-planning and selection of appropriate teaching-learning material in their classrooms for making inclusion as the universal and approachable concept.